Assessment of Nutritional Status, knowledge and practices of women attend fitness centers (GYM) at AL-Klakla Area, December, 2016 - Jihad Khider Ahmed Ibrahim, Dr .Suzan Ali yousif Abo*, Pro.Omer A.musa (Innovative Journal of Medical and Health Sciences, 2019)
The study objectives of this study were to assess the nutritional status, knowledge, awareness, and practices of women attending fitness (gym) centers at Alklakla locality, the sample included hundred (100) women had been chosen randomly from five different centers at ALklakla Questionnaire was used as tool to collect the data which included: socio demographic characteristics, sport information, medical history as well as nutritional and anthropometrics data. Data entry and analysis done through SPPS program by frequencies and cross tabulation. The results of the study showed that: The age of sample ranged from 20 to 35 years old. 46% of the sample belongs to the age group 20-24 years old. 50% were students at universities. Anthropometric measurements showed that: 70% were overweight, 48% their waist/hip ratio more than 85%. 53%) have joined gym to reduce their weight. 63% of women who attend gym knew it from their friends. Most of the women studied (63%) were not satisfied with their body shapes and the majority (78%) reported that exercising positively change their mood. Half of the women studied eat usually less than three meals daily (51%). 48% regularly take fast food three times or more per week, 46% of them used frying as the most common method of cooking their food. The study found that most of the women studied followed tough diet (low in energy, protein and fats); they depend on vegetables, soups, fruits and excluding meals to reduce calories (there exists an inadequacy in dietary intake of both macro and micronutrients). There was also lack knowledge about nutrition, healthy food choices and the component of a well-balanced diet. Therefore, this study recommends and stresses on the importance of the presence of dietitians at all gym centers as to help in improving these women nutrition awareness and the healthiest ways to lose weight. GYM: Means gymnasium, facility equipped for sports or physical training